A study to access knowledge of oral health, behavior and attitude of first and final year dental and medical students of Bareilly City, Uttarpradesh - Laxman Singh Kaira (Wolters Kluwer Medknow Publications, 2012)
Objective: To assess and compare differences in oral health knowledge, attitudes and behavior among first and final year dental And Medical students in Bareilly city, Uttarpradesh, India. Material and methods: In a cross-sectional study, 182 first year students (59 males and 123 females) and 157 final year students (75 males and 82 females) of the dental and medical college in Bareilly city; Uttarpradesh, were surveyed using a self administered structured questionnaire including 37 choice questions pre-tested through a pilot survey. The data was analyzed using the SPSS version 10.0. The mean percentage scores, standard deviation, and frequency distribution were calculated. The Student's T-test and ANOVA test were used as test of significance. The linear regression analysis was used to assess the relation of knowledge, attitude and behavior. Results: The mean % score for oral health knowledge, attitude and behavior were significantly higher in final year students compared to first year students. (p<0.001). The linear regression analysis showed a statistically significant linear relationship of attitude with the knowledge (p<0.001) and behavior with the attitude (p<0.001) of the students. Conclusion: Besides the positive changes revealed in the oral health knowledge, attitude and behavior, among the students from first to final year of dental and medical studies, preventive behavior among the students could still be improved.